Tekanan ekonomi, kekuatan keluarga dan harga kendiri anak - Arshat, Zarinah; Baharudin, Rozumah; Juhari, Rumaya; Abu Talib, Mansor (Jabatan Antropologi dan Sosiologi, Fakulti Sastera dan Sains Sosial, Universiti Malaya, 2009)
This study aims to determine the relationships between economic strain, family strength and children's self-esteem. A total of 200 parents with a focal child 7 to 12 years of age were selected. Respondents were interviewed face-to-face using a structured questionnaire. Economic strain was measured by Economic Strains Scale (Pearlin et al., 1981). Family strengths was assessed using Australian Inventory of Family Strengths (Geggie et al., 2000). Children's self-esteem was measured using Rosenberg Self-Esteem Scale (Rosenberg, 1965). Results show that the levels of economic strain, family strength and children's self-esteem were moderate. Economic strain was found to be associated negatively and significantly with family strength and children's self- esteem. While family strength was positively and significantly related to children's self-esteem. The study imply that the economic strain influence family strength, whereas children's self-esteem was influenced by economic strain and family strength.